2007
DOI: 10.1002/cncr.22848
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of mammography screening for Chinese women

Abstract: Low‐density polyethylene (LDPE) was treated with a low‐temperature cascade arc plasma torch (LTCAT) of argon with or without adding a reactive gas of oxygen or water vapor. The static sessile droplet method and the dynamic Wilhelmy balance method were employed to perform surface contact angle measurement in order to investigate and characterize the effects of LTCAT treatment on LDPE surfaces. These treatment effects included changes in surface wettability and surface stability and possible surface damage that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 55 publications
3
102
0
3
Order By: Relevance
“…There are also doubts in the cost-effectiveness of this preventive intervention. The study by Wong et al (2007) indicated that mammography for Hong Kong women might not be cost effective under the current scarce public health resources. Since mammogram screening is a low priority in public health care and is not recommended to the general female population, most women are unaware of its actual benefits.…”
Section: Discussionmentioning
confidence: 99%
“…There are also doubts in the cost-effectiveness of this preventive intervention. The study by Wong et al (2007) indicated that mammography for Hong Kong women might not be cost effective under the current scarce public health resources. Since mammogram screening is a low priority in public health care and is not recommended to the general female population, most women are unaware of its actual benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Tendo em vista o custo significativo da implementação de programas de rastreamento mamográfico, vários países avaliaram a custoefetividade dos mesmos, encontrando resultados heterogêneos dependendo dos pressupostos e parâmetros incluídos nos modelos econô-micos 6,7,8 . No Brasil, apenas um estudo publicado até agora avaliou o custo-efetividade do rastreamento mamográfico, porém comparando cenários de 100% e 0% de adesão ao rastreamento 9 -ambos pouco plausíveis.…”
Section: S132unclassified
“…[24] of the Swiss population-based breast cancer screening programme found a cost effectiveness ratio of 11,500 Euro per YLS and a retrospective study of the American programme estimated the costs to be 24,700 Euro per QALY gained [25]. In China, an estimate of CE- and CU-ratios of ~ 58,900 Euro per YLS and 56,400 Euro per QALY gained were concluded [26]. In contrast, the most favourable option found in this paper was regional screening with accommodation in regular hotels, which encompassed 0.5 million DKK (67,500 Euro)/YLS and 3.9 million DKK (0,53 million Euro)/QALY gained.…”
Section: Discussionmentioning
confidence: 99%
“…Only under the most favourable model assumptions were the CU-ratios comparable with the results by Wong et al . [26], where the authors concluded that the scarce resources in society might be better used elsewhere.…”
Section: Discussionmentioning
confidence: 99%